Magnetic resonance imaging signs of iliotibial band friction in patients with isolated medial compartment osteoarthritis of the knee - Vasilevska Nikodinovska, Violeta; Szeimies, Ulrike; Stäbler, Axel (Springer Science and Business Media LLC, 2009)
Background The purpose of this retrospective study was to assess the frequency of magnetic resonance imaging (MRI) signs of iliotibial band friction (ITBF) in patients with advanced medial compartment knee osteoarthritis. Material and methods Proton density-weighted (PDw) fat-saturated (fatsat) MR images (1.5 T, slice thickness (SL) 2.5–3 mm, eight-channel phased array coil) of 128 patients with isolated advanced osteoarthritis of the medial knee compartment and complete or subtotal (>80%) loss of cartilage were evaluated. There were 41 men and 87 women. Mean age was 63 years, range 34–89 years. The control group consisted of 94 patients with medial meniscus degeneration without cartilage loss (56 men and 38 women, mean age 50 years, range 16–89 years). MRI signs of ITBF were evaluated in both groups [poorly defined abnormalities of signal intensity and localized fluid collection lateral, distal or proximal to the lateral epicondyle; signal intensity abnormalities superficial to or deep by the iliotibial band (ITB)]. Transverse images were evaluated separately. Consensus evaluation using all imaging planes was performed. Results Of 128 patients with osteoarthritis, 95 had moderate or advanced MRI signs of ITBF (74.2%). Eighty-nine patients (69.5%) had advanced degeneration of the meniscus. In the control group, 26 of 94 patients had only moderate MRI signs of ITBF. There was a statistically significant difference between both groups for the presence of MR signs of ITBF (P ≤ 0.01). Conclusion MRI signs of ITBF were frequently present in patients with severe medial compartment osteoarthritis of the knee. Joint space narrowing with varus knee deformity may be a cause of ITBF.
Keywords: Iliotibial band friction syndrome; Medial compartment osteoarthritis/osteoarthrosis of the knee; Magnetic resonance imaging (MRI)